Aspirin is associated with reduced cartilage loss in knee osteoarthritis: Data from a cohort study. Issue 3 (July 2015) - Wluka, Anita E.; Ding, Changhai; Wang, Yuanyuan; Jones, Graeme; Urquhart, Donna M.; Cicuttini, Flavia M.
Graphical abstract